Reavaliação ecotoxicológica da qualidade da água e do sedimento do reservatório da Pampulha (MG) e seus principais tributários - Suellen Cristina Moreira de Sales (2009)
Pampulha Reservoir, an important site in the history of Belo Horizonte, is currently at a high level of degradation and contamination. In this context, this study aimed to evaluate the quality of water and sediment of Pampulha reservoir, from the ecotoxicological point of view, complementing studies from 1998 prior to installation of a treatment station for superficial waters (ETAF-COPASA) and other interventions. Three campaigns on six sampling stations were carried out, including three inside the reservoir, two in Sarandi and Ressaca streams and one in the treatment station ETAF-COPASA, in March and April (rainy season) and August (dry season) of 2008. Bioassays of acute and chronic toxicity of water sediment and interstitial water were conducted in the laboratory Ceriodaphnia silvestrii, Daphnia similis, Daphnia laevis and Chironomus xanthus as bioindicators and metals were determined in water and sediment samples. The results showed both acute and/or chronic toxicity effects in water samples at all sampling sites. In the rainy season,Pampulha reservoir showed intense bloom of algae, which may have been responsible for the effect of water acute toxicity. In the dry period, it was verified effect of chronic toxicity only at points outside the reservoir. For the sediment, toxicity effects were detected for all sampling sites, in the two seasons considered. The levels of Cu, Cd, Fe andMn in the water exceeded limits established by CONAMA 357, at all sampling sites. In the ETAF-COPASA, Zn was detected above the levels permitted by legislation (182 mg. L-1).In the sediment, levels of zinc exceeded limits established by CONAMA 344. The point after ETAF-COPASA (outflow) showed the highest level of contamination for Cr (91.45g.g-1), Cu (46.27 g.g-1) and Zn (704.97 g.g-1). Thus, the effects of toxicity could have been related to metals and also to a bloom of toxic algae. Compared with previous studies,there was reduction in water and sediment quality of Pampulha reservoir and its maintributaries. ETAF/COPASA, which initiated its activities in 2003, was one of the mostimpacted sites, presenting an increase of iron by treatment.